2020
DOI: 10.1590/1980-0037.2020v22e65027
|View full text |Cite
|
Sign up to set email alerts
|

Percentile curves for Brazilian children evaluated with the Bruininks-Oseretsky Test of Motor Proficiency, 2nd edition

Abstract: This study aimed to (1) create percentile curves and norms for the eight subtests of the Bruininks-Oseretsky Test of Motor Proficiency, 2 nd edition (BOT-2) for 6-to 10-year-old Brazilian children and to (2) compare them to the values of the original test manual. To that, we tested a sample of 931 Brazilian children (477 girls, 454 boys) with ages between 6 to 10 with the BOT-2 assessment. The LMS method was used to generate the percentile curves and normative values, with the LMSchartmaker Pro software versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…One study did show evidence of the BOT being a reliable measure of FMS in children with intellectual deficits [65]. One study explored the cross-cultural validity of the BOT-2 norm scores with a large Brazilian sample (n = 931) and found mixed results [79]. Results showed that Brazilian children outperformed the BOT normative data on bilateral coordination, balance, upper-limb coordination, and running speed and agility subtests, but similar percentile curves were found for both populations on upper limb coordination and balance subtests [79].…”
Section: Bruininks-oseretsky Test Of Motor Proficiency (Bot)mentioning
confidence: 99%
See 1 more Smart Citation
“…One study did show evidence of the BOT being a reliable measure of FMS in children with intellectual deficits [65]. One study explored the cross-cultural validity of the BOT-2 norm scores with a large Brazilian sample (n = 931) and found mixed results [79]. Results showed that Brazilian children outperformed the BOT normative data on bilateral coordination, balance, upper-limb coordination, and running speed and agility subtests, but similar percentile curves were found for both populations on upper limb coordination and balance subtests [79].…”
Section: Bruininks-oseretsky Test Of Motor Proficiency (Bot)mentioning
confidence: 99%
“…(Continued) evaluating the validity and reliability of FMS assessment tools were conducted in 29 countries, with Australia hosting the most studies(13) [50,56,[71][72][73][74][75][76][77], followed by Brazil (12 studies)[53,57,66,70,[78][79][80][81][82][83][84][85] and the USA (nine studies). Eight studies were carried out in Belgium[49,58,63,[86][87][88][89] and seven in Canada[43,54,60,[90][91][92][93][94].…”
mentioning
confidence: 99%
“…The level of motor proficiency was assessed by the BoT TM -2 CF testing battery relative to the changes from baseline; main outcome variables from pre-to post-intervention. BoT TM -2 CF is a norm-referenced standardised test designed to assess fine and gross MSs for children and individuals aged between 4 and 21 years [35,36]. The children were tested using the complete form of the BoT TM -2 CF, which is available with four composite areas [e.g., (a) fine manual control, (b) manual control, (c) body control, (d) strength and agility] and eight subtests [e.g., (1) fine manual precision, (2) fine motor integration, (3) manual dexterity, (4) upper-limb coordination, (5) bilateral coordination, (6) balance, (7) running speed and agility, (8) strength].…”
Section: Instrumentsmentioning
confidence: 99%
“…The BoT TM -2 CF was chosen in our study because it is one of the most comprehensive assessments for motor proficiency worldwide. it evaluates a diverse range of MS and is frequently used in the international diagnostic guidelines, and in research studies of functional capacity in children and school-age young adults as a reliable assessment tool [36].…”
Section: Instrumentsmentioning
confidence: 99%
“…Despite the existence of an instrument qualified as a gold pattern to assess the development and motor coordination, nowadays, there are in literature, multiple instruments that have been proposed in different areas of The Science of Sport: the Test of Gross Motor Development (TGMD-2), Movement Assessment Battery for Children, 2nd edition (MABC-2), Körperkoordinationstest Für Kinder (KTK), Bruininks-Oseretsky Test of Motor Proficiency, 2nd Edition (BOT-2), Motor Development Scale (MDS), Basic Motor Competencies Assessment-MOBAK and the Motor Coordination Test with Ball-TECOBOL among others [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%